Effect of Water and Nutrient Supply on the Allelopathy of Abutilon theophrasti Medic. and Xanthium italicum Mor - Dávid, István (Acta Agraria Debreceniensis, 2003)
Velvetleaf (Abutilon theophrasti Medic.) and Cocklebur species (Xanthium spp.) are more and more dangerous and „difficult to control” weeds in several cultivated plants. The ground cover of these species have became larger in Hungary like other warm-philous species. There are several causes of danger of them, for example: large capability for competition, allelopathic effect, keeping on of emergence.The allelopathic effect of these weeds were examined on sugarbeet (Beta vulgaris L.). Extracts of plants grown under different conditions have several effect on this species.Abutilon theophrasti plants were grown in perlite to examine the effect of supplying with nutritive materials on production of inhibitors. The water soluble exudates of the shoots grown with no artificial fertilisers inhibit stronger than grown with them. Acid soluble exudates have contrary effect. The exudates made of roots inhibited the sugarbeet less than shoots.Effect of drought stress on production of inhibitors was examined on Abutilon theophrasti and on Xanthium italicum. The species responded to missing of water different, and the water, acid and basic soluble exudates had different effect, as well.